2011
DOI: 10.1063/1.3589304
|View full text |Cite
|
Sign up to set email alerts
|

Particle energization in 3D magnetic reconnection of relativistic pair plasmas

Abstract: We present large scale 3D particle-in-cell (PIC) simulations to examine particle energization in magnetic reconnection of relativistic electron-positron (pair) plasmas.The initial configuration is set up as a relativistic Harris equilibrium without a guide field. These simulations are large enough to accommodate a sufficient number of tearing and kink modes. Contrary to the non-relativistic limit, the linear tearing instability is faster than the linear kink instability, at least in our specific parameters.We … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
81
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(91 citation statements)
references
References 22 publications
(64 reference statements)
10
81
0
Order By: Relevance
“…Magnetic islands then become extended filaments, modulated or broken by instabilities in the third dimension or by a lack of coherence of the tearing instability (Jaroschek et al 2004;Zenitani & Hoshino 2008;Daughton et al 2011;Liu et al 2011;Kagan et al 2013;Markidis et al 2013). For this reason we may expect more particle mixing, but current sheet particles may also still be trapped in the strong magnetic structure surrounding the filaments.…”
Section: Open Questionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Magnetic islands then become extended filaments, modulated or broken by instabilities in the third dimension or by a lack of coherence of the tearing instability (Jaroschek et al 2004;Zenitani & Hoshino 2008;Daughton et al 2011;Liu et al 2011;Kagan et al 2013;Markidis et al 2013). For this reason we may expect more particle mixing, but current sheet particles may also still be trapped in the strong magnetic structure surrounding the filaments.…”
Section: Open Questionsmentioning
confidence: 99%
“…In addition, since the island edges are the place A&A 570, A112 (2014) of strong motional electric fields, particles can gain energy there without necessarily turning around the whole island. Liu et al (2011) report that in their relativistic pair plasma simulations, most particles are energized in this way. Jaroschek et al (2004) also find that this scenario is important.…”
Section: Introductionmentioning
confidence: 99%
“…Previous reconnection studies have identified that particles are accelerated close to the reconnection X-point (Hoshino et al 2001;Drake et al 2005;Fu et al 2006;Oka et al 2010;Egedal et al 2012Egedal et al , 2015Wang et al 2016), in contracting magnetic islands (Drake et al 2006;Oka et al 2010), and also in island-merging regions (Oka et al 2010;Liu et al 2011;Drake et al 2013;Nalewajko et al 2015). At the X-points, particles get accelerated by streaming along the nonideal electric field.…”
Section: Introductionmentioning
confidence: 99%
“…Most previous kinetic studies focused on the non-relativistic regime σ < 1 and reported several acceleration mechanisms such as acceleration at X-line regions [7][8][9] and Fermi-type acceleration within magnetic islands [8][9][10][11]. More recently, the regime σ = 1-100 has been explored using pressure-balanced current sheets and strong particle acceleration has been found in both diffusion regions [12][13][14][15] and island regions [16,17]. However, this initial condition requires a hot plasma component inside the current sheet to maintain force balance, which may not be justified for high-σ plasmas.…”
mentioning
confidence: 99%